Effects of Ovariectomy and Dieting with Nano Calcium Phosphate on Bone Quality in White Rats Rattus norvegicus - Mulyaningsih, Neng Nenden; Juwono, Ariadne Lakshmidevi; Soejoko, Djarwani Soeharso; Astuti, Dewi Apri (Trends in Sciences, 2022)
Calcium supplements are widely used to prevent osteopenia and osteoporosis and can be used as a treatment along with other drugs. The effect of this supplement can be seen from the improved bone quality. The focus in this study was to analyze the quality of femur bone based on the mineral maturity and the degree of crystallinity from ovariectomized Rattus norvegicus where the treatment of various nano calcium phosphate diets (1.0×; 1.5× and 2.0× normal needs, respectively called A, B and C diets) also given. In the amount of 40 white female rats age 12 weeks were ovariectomized and 5 sham rats were nurtured. The group of sham was given euthanasia treatment at age 13 weeks, while ovariectomized group was treated euthanasia at age 17 and 21 weeks. At the age of 25 weeks after ovariectomy, the rats were treated with a nano calcium phosphate diet where analysis was performed when they were 31 and 40 weeks old. In each harvest, proximal femur part was collected and characterized by using FTIR Spectroscopy. Rat bone quality shows osteoporosis trait for the first time at age 21 weeks or after 9 weeks of ovariectomy with the mineral maturity and degree of crystallinity decreased in the amount of 1.16 and 2.27 %, respectively compared to femur bone from sham rat group. The dietary treatment study conducted showed that the group of rats fed the A diet had not a significant changes (p < 0.05) in the mineral maturity and the degree of crystallinity, while giving B or C diet had a significant increase in the mineral maturity at 40 weeks of age or after 15 weeks on a diet. The increase in the degree of crystallinity of the rats fed B diet (6 weeks) was faster than the group fed C diet (15 weeks). Therefore, diet B is recommended because it is more efficient and effective based on the time it increases the degree of crystallinity and the cost of producing the diet. HIGHLIGHTS Ovariectomy is one of the treatments that can condition the bones of rats to have osteoporosis. One of the bone parts of rats that are often affected by osteoporosis is the femur Bones of rats that have osteoporosis can be restored by giving a nano calcium phosphate diet Parameters that can be analyzed regarding the decline and improvement of bone quality include mineral maturity and the degree of crystallinity. Assessment of these parameters can be done using Fourier Transform Infrared Spectroscopy GRAPHICAL ABSTRACT